Proteome Birthdating: A Single-Sample Approach for Measuring Global Turnover Dynamics and “Protein Age” - Michael Meadow; Sarah Broas; Margaret Hoare; Maria Ahmed; Fatemeh Alimohammadi; Kevin Welle; Kyle Swovick; Jennifer Hryhorenko; Anushka Jain; John Martinez; Andrei Seluanov; Vera Gorbunova; et al. (Bio-Protocol)
Within a cell, proteins have distinct and highly variable half-lives. As a result, the molecular ages of proteins can range from seconds to years. How the age of a protein influences its environmental interactions is a largely unexplored area of biology. To facilitate such studies, we recently developed a technique termed “proteome birthdating” that differentially labels proteins based on their time of synthesis. Proteome birthdating enables analyses of age distributions of the proteome by tandem mass spectrometry (LC–MS/MS) and provides a methodology for investigating the protein age selectivity of diverse cellular pathways. Proteome birthdating can also provide measurements of protein turnover kinetics from single, sequentially labeled samples. Here, we provide a practical guide for conducting proteome birthdating in in vitro model systems. The outlined workflow covers cell culture, isotopic labeling, protein extraction, enzymatic digestion, peptide cleanup, mass spectrometry, data processing, and theoretical considerations for interpretation of the resulting data.